SAT0010 A Targeted Next-Generation Sequencing Gene Panel for Autoinflammation. (15th July 2016) - Omoyinmi, E.; Standing, A.; Keylock, A.; Rowczenio, D.; Melo Gomes, S.; Cullup, T.; Jenkins, L.; Gilmour, K.; Eleftheriou, D.; Lachmann, H.; Hawkins, P.; Klein, N.; et al.
Abstract : Background: Monogenic autoinflammatory diseases (AID) are severe lifelong systemic inflammatory disorders with dysregulated innate immunity, causing significant morbidity, mortality, and economic burden. The number of AID is rapidly expanding. Securing a molecular diagnosis is of major importance for treatment, prognosis, and genetic counselling. Routine genetic screening is time-consuming, costly, and lacks sensitivity since only common disease harbouring exons of a minority of the known AID genes are currently tested using Sanger sequencing. Next-generation sequencing (NGS) offers the ability to rapidly and cost-effectively screen all exons of a gene panel containing hundreds of genes. This approach has not yet been routinely introduced in the UK for AID. Objectives: To develop and evaluate the performance of a NGS gene panel for AID. Methods: The Agilent SureDesign tool was used to design an NGS panel targeting 113 genes, grouped into 9 broad clinical phenotypes: AID; monogenic vasculitis/vasculopathy; complement defects; monogenic lupus; hemophagocytic lymphohistiocytosis (HLH); early-onset inflammatory bowel disease; autoimmune lymphoproliferative syndromes; monogenic stroke; and hereditary amyloidosis. The targeted region includes coding exons, conserved non-coding exons, upstream promoter regions, and splice sites. Captured and indexed libraries (QXT Target Enrichment System) were sequenced as a multiplex of 16 samples on an Illumina MiSeq sequencer in paired-end mode. Positive controls for panel validation comprised 19 DNA samples from patients with confirmed mutations in a variety of genes on the panel. We then applied the panel to test 29 prospective samples with suspected but unconfirmed monogenic inflammation. Read alignment, variant calling, and annotation were performed using Agilent SureCall v3.0 software. Results: In the validation stage, our targeted panel detected all known mutations in the 19 positive control samples with an average read depth of 244X (+/− 29X) across the captured genes. The panel was effective at detecting different types of variants, including rare and common single nucleotide variants (SNVs), insertion/deletions, splice-junction variants, upstream promoter region variants, and somatic mosaicism. Prospective testing of the panel in 29 patients revealed potential pathogenic variants in 14 of the 29 patients giving a detection rate of 48%. These included atypical patients with novel mutations in specific exons/genes, not currently routinely available for testing by Sanger sequencing in the NHS. Conclusions: This study demonstrates the clinical utility of a comprehensive NGS-based targeted gene panel which was both highly sensitive and specific in detecting different sequence variants of clinical significance. We are currently integrating this panel into a routine diagnostic laboratory testing strategy for monogenic inflammation. This will facilitate accurate and timely molecular diagnosis, more targeted treatment, and ultimately better outcomes for our patients. Acknowledgement: This work was supported by Rosetrees Trust and Swedish Orphan Biovitrum (SOBI). Disclosure of Interest: None declared